2020
DOI: 10.1111/cea.13746
|View full text |Cite
|
Sign up to set email alerts
|

Expression of ACE2 in airways: Implication for COVID‐19 risk and disease management in patients with chronic inflammatory respiratory diseases

Abstract: The current outbreak of coronavirus disease 2019 (COVID-19), which was first reported in December 2019, spreads across the globe rapidly and has been declared as pandemic on 11 March 2020 by the World Health Organization. 1-4 COVID-19 is caused by a novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and associates with substantial morbidity and mortality. 2-8 As of 19 July 2020, more than 14.0 million cases have been confirmed and over 600,000 deaths. The clinical manifestations of COVID-19 are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
72
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 131 publications
(366 reference statements)
3
72
0
3
Order By: Relevance
“…However, our study may strengthen the current understanding of the impact of the pandemic on all subgroups of PID and highlights the requirement of tight measurements in children affected mainly with combined immunodeficiency and immune dysregulation. Of note, several recent studies identified that lymphopenia with prominent decreased T cell (mainly CD8 + cytotoxic T cell) counts are associated with severe COVID-19 condition and mortality [3,[28][29][30][31]. Indeed, lymphopenia seems to correlate with the cytokine profile of the severe patients which resemble our observation in PID patients [30,32].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…However, our study may strengthen the current understanding of the impact of the pandemic on all subgroups of PID and highlights the requirement of tight measurements in children affected mainly with combined immunodeficiency and immune dysregulation. Of note, several recent studies identified that lymphopenia with prominent decreased T cell (mainly CD8 + cytotoxic T cell) counts are associated with severe COVID-19 condition and mortality [3,[28][29][30][31]. Indeed, lymphopenia seems to correlate with the cytokine profile of the severe patients which resemble our observation in PID patients [30,32].…”
Section: Discussionsupporting
confidence: 85%
“…ACE2 receptor is ubiquitously expressed on the surfaces of various cell types, including cells of the airway epithelium which is the major site of infection [2]. Besides the ACE2 receptor, SARS-CoV-2 uses the transmembrane serine protease 2 (TMPRSS2), a cellular serine protease, for the host cell entry, which activates the SARS-CoV-2 spike protein by cleaving the Furin site at the S1/S2 subunits [3,4]. Upon entry, the virus can subsequently affect endosomes, and eventually, fuse viral and lysosomal membranes [5].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several studies showed that IL-13 downregulated ACE-2 expression not only in bronchial epithelial cells but also in nasal epithelial cells. 37 Considering the studies done so far, AR does not appear to be a risk factor for COVID-19 either.…”
Section: Discussionmentioning
confidence: 90%
“…Currently, the emerging evidence is that early Ct values from a nasopharyngeal swab correlate with disease susceptibility (age and comorbidities, such as smoking and hypertension, both associate with potential differential expression of ACE2 receptor [ 41 , 42 ]) and clinical presentations and predict disease severity, survival, and sequelae in symptomatic patients.…”
Section: Discussionmentioning
confidence: 99%